Defect‐Free Metal Deposition on 2D Materials via Inkjet Printing Technology. Issue 48 (21st November 2021) - Zheng, Wenwen; Saiz, Fernan; Shen, Yaqing; Zhu, Kaichen; Liu, Yingwen; McAleese, Clifford; Conran, Ben; Wang, Xiaochen; Lanza, Mario
Abstract: 2D materials have many outstanding properties that make them attractive for the fabrication of electronic devices, such as high conductivity, flexibility, and transparency. However, integrating 2D materials in commercial devices and circuits is challenging because their structure and properties can be damaged during the fabrication process. Recent studies have demonstrated that standard metal deposition techniques (like electron beam evaporation and sputtering) significantly damage the atomic structure of 2D materials. Here it is shown that the deposition of metal via inkjet printing technology does not produce any observable damage in the atomic structure of ultrathin 2D materials, and it can keep a sharp interface. These conclusions are supported by abundant data obtained via atomistic simulations, transmission electron microscopy, nanochemical metrology, and device characterization in a probe station. The results are important for the understanding of inkjet printing technology applied to 2D materials, and they could contribute to the better design and optimization of electronic devices and circuits. Abstract : The evaporation of Au or the sputtering of Cr on 2D layered hexagonal boron nitride (h‐BN) produces local atomic defects in its structure, specially at its interfaces, which increases the leakage current across it. It is found that the deposition of metal on hexagonal boron nitride (h‐BN) using inkjet printing does not introduce any defect, and maintains its layered structure free of defects.